A argumentação na obra O abolicionismo de Joaquim Nabuco: uma perspectiva historiográfica - Volpato, Luno (2007)
The topic of our study is the argumentation about the composition of Joaquim Nabuco, O abolicionismo. The target is the knowledge of the argumentative resources and the linguistic resources that construct this argument, applying the principles of the Linguistic Historiography, to know, the Contextualization, the Immanency and of the Adequacy. Always instigated us to know closer the illustrious brazilian, Joaquin Nabuco. In the second half of the century XIX, in full literary bubbling, among others excellent names, Joaquin Nabuco obtained a place of preeminence among his pairs. This detail, and for the fact of his composition not to be divulged as other classics of our language, showed us a singular attention and we went to the search of the elements that had taken him to become an expressive figure at his time. He has written a composition in defense of the slaves emancipation, O abolicionismo, object of this research. To know it better, we considered the following questions that had directed our study: Which were the argumentative and linguistic resources made for the author and, with them, how has the author reached his public, the oitocentista reader? Which was his audience? Has the nabuconeana language followed the linguistic molds of its time? In full movement of freedom which was the language used by him, the classic of Portugal or the Brazilian dialect? Which current literary has he belonged? Can his language be considered out of the time? Guided for these questions, we looked more details in his composition, over all in what concerns to the strategies for him used for the adhesion of his personage, the way he chooses the proves, how he trams the arguments, and the progression to make the hierarchy and how it intensifies during the advance of the chapters of the book. To reach this objective, we follow the three principles considered for Koerner: of the contextualization, where it creates the climate opinion, of the immanency, where it analyzes the corpus on the basis of the classic Rhetoric and the adequacy, where it brings up to date the previous analysis, with bedding in a modern theory, the New Rhetoric. After the analysis, we´ve got the results